Influence of Brand Communication, Online Brand Community, and Service Quality with Brand Trust as the Mediator towards Brand Quality for Agriculture Fintech Company. Empirical Study: PT Crowde Membangun Bangsa - Oscar, Oscar; Tanuwijaya, Jennifer Leonita (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This study aims to analyze the influence of brand communication on brand trust, the influence of online brand community on brand trust, the influence of service quality on brand trust, the influence of brand trust on brand loyalty, the influence of brand communication on brand loyalty, the influence of online brand community on brand loyalty, the influence service quality on brand loyalty, the influence of brand communication on brand loyalty mediated by brand trust, the influence of online brand community on brand loyalty mediated by brand trust, the influence of service quality on brand loyalty mediated by brand trust. The research respondents were 393 investors as users of the Crowde P2P lending platform and 385 farmers as Crowde's partners. The method used is a survey using a Likert scale questionnaire. Data processing is done with PLS 3.2.5 to analyze five variables namely brand communication, online brand community, service quality, brand trust, and brand loyalty. The results showed that (1) brand communication affects brand trust positively and significantly for investors and farmers, (2) online brand community affects brand trust positively and significantly for investors but not significantly for farmers, (3) service quality affects brand trust positively and significantly for investors and farmers, (4) brand trust affects brand loyalty positively and significantly for investors and farmers, (5) brand communication affects brand loyalty positively and significantly for investors but for farmers the results are negative and significant, (6 ) online brand community influences brand loyalty positively and significantly on investors and farmers, (7) service quality affects brand loyalty positively and significantly for investors but for farmers the results are negative and significant, (8) brand communication influences brand loyalty mediated by brands trust positively and significantly to investors and farmers, (9) online brand community influences brand loyalty which is mediated by brand trust positively but not significantly on investors and farmers, (10) service quality influences brand loyalty which is mediated by brand trust positively and significantly on investors and farmers.